Harry Potter and the Order of the Phoenix J.K. Rowling; Illustrated by Mary GrandPre - Rowling, J. K.; GrandPre, Mary (New York, NY : Arthur A. Levine Books, 2003)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.
"Year 5"--Spine.
Sequel to: Harry Potter and the goblet of fire.
950
86105
Keywords: Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; Coming of age -- Fiction; Potter, Harry (Fictitious character) -- Juvenile fiction; Wizards -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Juvenile fiction; England -- Juvenile fiction; Fantasy fiction, Juvenile; Juvenile materials